Career and work attitudes of blue-collar workers, and the impact of a natural disaster chance event on the relationships between intention to quit and actual quit behaviour. Issue 3 (3rd May 2016) - Baruch, Yehuda; Wordsworth, Russell; Mills, Colleen; Wright, Sarah
Abstract : Despite being part of a highly visible and important occupational group, blue-collar workers have, to date, been under-represented in careers research. We explore the relevance and applicability of new career concepts to blue-collar employees, specifically, bus drivers. Based on a survey of 112 bus drivers, we test a model specifying the relationship between career attitude, perceived organizational support, psychological contract, and job satisfaction, as well as intention to quit. Employing a two-phase data collection process, we also test relationships between intentions and actual quit behaviour. Our results support the validity of career theories for blue-collar workers but with notable exceptions, such as lack of relationships between protean career and intention to quit. Contrary to intention-behaviour theory we find that actual quit behaviour was not related to intention to quit, which we attribute to a significant external chance event, a devastating earthquake, which took place during the study period. In addition, we identify relationships that appear to be unique to blue-collar workers.